Pendekatan Analisis Multivariat dan Ekonometrika Spasial dalam Pemodelan Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi Pulau Jawa (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Economic growth is one of the key indicators that reflects the welfare level of a country's population. Therefore, economic growth is always a central focus in national development planning, with the expectation of continuous improvement year after year. Java Island plays a vital role as the largest contributor to the national economy. However, the impact of the Covid-19 pandemic, which occurred recently, caused a significant economic contraction, and Java Island was the most affected region. This crisis has impacted all sectors of the economy, including industry, trade, and tourism, which in turn affected the national economy. Nevertheless, the economic recovery efforts have begun to show results, with the economy, especially in Java, growing significantly in 2021. However, rapid growth in certain districts/cities in Java has caused new issues, such as population explosions, environmental degradation, and increasing crime rates. Therefore, it is essential to conduct a thorough analysis of the factors influencing economic growth and to map out the potential economic indicators in various regions across Java. This study uses multivariate biplot analysis and spatial econometrics to analyze and map the uniformity of districts/cities, industry mapping, and areas that serve as growth centers and those that are less developed. The results show that factors affecting economic growth in districts/cities vary. Generally, inflation has both positive and negative effects on the economy, while the unemployment rate, human development index, and population growth rate have a positive impact on economic growth. This study provides clear insights to support more targeted and effective development policies on Java Island, as well as improve the quality of life for residents in less developed areas.